2021
DOI: 10.3389/feart.2021.673124
|View full text |Cite
|
Sign up to set email alerts
|

Can Hydrocarbon Extraction From the Crust Enhance or Inhibit Seismicity in Tectonically Active Regions? A Statistical Study in Italy

Abstract: A number of oil- and gas-producing leases have been operating in Italy in the last decades, many of which are located in the surroundings of tectonically active regions. Identifying human-induced seismicity in areas with high levels of natural seismicity is a difficult task for which virtually any result can be a source of controversy. We implemented a large-scale analysis aiming at tracking significant departures of background seismicity from a stationary behavior around active oil and gas development leases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Early attempts to discriminate induced from natural seismicity were performed, for fluid injection operations, by Davis and Frohlich (1993), and for fluid withdrawal by Davis and Nyffenegger (1995); however, these approaches were mainly based on qualitative assessments. More quantitative approaches, based on physical and/or stochastic features of recorded seismicity also have been proposed in literature (a review can be found, e.g., in Dahm et al, 2015;Schoenball et al, 2015;Grigoli et al, 2017;Garcia et al, 2021). In principle, evaluating possible interactions between seismicity and hydrocarbon production should rely on multidisciplinary analyses such as detailed physically-based modelling and stochastic methods.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Early attempts to discriminate induced from natural seismicity were performed, for fluid injection operations, by Davis and Frohlich (1993), and for fluid withdrawal by Davis and Nyffenegger (1995); however, these approaches were mainly based on qualitative assessments. More quantitative approaches, based on physical and/or stochastic features of recorded seismicity also have been proposed in literature (a review can be found, e.g., in Dahm et al, 2015;Schoenball et al, 2015;Grigoli et al, 2017;Garcia et al, 2021). In principle, evaluating possible interactions between seismicity and hydrocarbon production should rely on multidisciplinary analyses such as detailed physically-based modelling and stochastic methods.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%
“…These latter may provide probabilistic assessments and take uncertainties into account (Segall, 1989;Segall et al, 1994;Gishig and Wiemer, 2013;Dahm et al, 2015;Schoenball et al, 2015;Grigoli et al, 2017;Garcia-Aristizabal, 2018, among others). Even though, the ways in which the interactions may occur are complex, and their identification in a context characterised by naturally-occurring seismicity is not straightforward (Garcia et al, 2021). These reasons stimulate the implementation of alternative statistical methods to track measurable phenomena, as changes in seismicity rates.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%
“…Early attempts to discriminate induced from natural seismicity were performed, for fluid injection operations, by Davis and Frohlich (1993), and for fluid withdrawal by Davis and Nyffenegger (1995); however, these approaches were mainly based on qualitative assessments. More quantitative approaches, based on physical and/or stochastic features of recorded seismicity also have been proposed in literature (a review can be found, e.g., in Dahm et al, 2015;Schoenball et al, 2015;Grigoli et al, 2017;Garcia et al, 2021). In principle, evaluating possible interactions between seismicity and hydrocarbon production should rely on multidisciplinary analyses such as detailed physically-based modelling and stochastic methods.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%
“…These latter may provide probabilistic assessments and take uncertainties into account (Segall, 1989;Segall et al, 1994;Gishig and Wiemer, 2013;Dahm et al, 2015;Schoenball et al, 2015;Grigoli et al, 2017;Garcia-Aristizabal, 2018, among others). Even though, the ways in which the interactions may occur are complex, and their identification in a context characterised by naturally-occurring seismicity is not straightforward (Garcia et al, 2021). These reasons stimulate the implementation of alternative statistical methods to track measurable phenomena, as changes in seismicity rates.…”
Section: Pore Pressure Monitoringmentioning
confidence: 99%